Decommissioned batteries and their usage in multilevel inverters as an addition to the circular economy. Issue 4 (21st January 2022) - Hamid, Muhammad; Li, Boyang; Xie, Jian
Abstract: Research on decommissioned batteries emphasizes the value of lost energy in batteries. This article analyzes the leftover battery capacity after its decommissioning from electric vehicles. This analysis includes the discreteness of the battery capacity, sorting based on a QC/T‐standard and alteration among the battery capacities. The potential of decommissioned batteries in other applications is presented, and a roadmap for the circular economy is suggested. Based on the data collected in China, significant faults occurring inside electric vehicles' battery packs are reviewed. An alternative inverter is tested to solve the significant challenges in using decommissioned batteries. Advancements are made toward a new intuitive cell balancing technique to utilize maximum capacity in each cell.